Study of antioxidant potential in averrhoe carambola l. and citrus maxima merr. by colorimetric assay - Chua, Hui Ching (2013)
There is increasing interest in the biological activity of plant phenolics and flavonoids outlined the necessity of determining their content in plant sources. The therapeutic effects of phenolics and flavonoids can be largely attributed to their antioxidant properties. The aim of this study is to investigate the antioxidant potential of aqueous and ethanol extracts of local fruits, Averrhoe carambola L. and Citrus maxima Merr. in Malaysia. Quantitative determinations were undertaken on total phenolics content and total flavonoids contents based on UV-spectrophotometric method. The average total phenolic content of ethanol and aqueous extract in A. carambola was found to be 71.34 ± 9.15 and 87.49 ± 12.11 mg GAE/100g respectively. Whereas the average total flavonoid content showed the values of 42.67 ± 2.41 and 17.67 ± 1.18 mg QE/100g in A. carambola extracts. In case of C. maxima, higher total phenolic and total flavonoid contents were observed in aqueous extract i.e. 34.94 ± 3.27 mg GAE/100g and 30.17 ± 1.18 mg QE/100g. In contrary, ethanol extract of A. carambola showed the highest phenolic and flavonoid values. The TPC of studied fruits with respected to ethanol and aqueous solution are not significant (P>0.01) unlike TFC (P<0.01). The results revealed that both fruits have different antioxidant potential and A. carambola can be regarded as promising candidates for natural plant sources of antioxidants.